Az akadálymentesítés gyakorlata a tamásiban megvalósuló ability projekt példáján - Kiss, Nikoletta; Dávid, Lóránt (Acta Carolus Robertus, 2011)
The ENSZ survey showed that 650 million people live with disabilities worldwide, of which 50 million in Europe. Concerning Hungary, the number of disabled people was 577 thousand in 2001, which is 5.77% of the total population. These numbers show very negative results in the tourism sector in the supply projection. People with disabilities - to be physically disabled, hearing impaired, visually impaired - unfortunately in our country have limited opportunities to travel, recreate go on "holiday" and for rehabilitation. In my thesis about the "Ability Park Tamási implemented pilot project I will highlight the importance of this sector of tourism (both economically and for people with disabilities, to be created in Hungary concerning a unique tourism product), I want to replace the kind of attitudes, because as people with disabilities are entitled to full life like everyone else.
Keywords: equal opportunity; accessible tourism; disabilities; hotel; bath